Interprofessional Education: Designing And Evaluating The Feasibility of Competency Based Interprofessional Educational Model In Orthodontics - Niranjane, Priyanka; Mishra, Vedprakash; Digavane, Pallavi (International Journal of Psychosocial Rehabilitation, 2020)
Aim- To design and evaluate the feasibility of competency based interprofessional educational model in Orthodontics. Method – As a part of need assessment, information on the current scenario of interprofessional education and collaborative practices in Dentistry in India will be gained from academic and administrative heads of those dental colleges having more than one health professional institutions in the same campus across India in the form of questionnaire survey. Profession-specific and Interprofessional Gap Analysis will be done to determine which IPE competencies are addressed in existing post graduate Orthodontic curricula, which topics best require a collaborative patient centred care, what pedagogical methods are used and how the competencies are assessed. A questionnaire survey will be formulated to gain above information from Orthodontic faculty having more than 5 years experience in the speciality. Need assessment from post graduate Orthodontic students will be conducted through interdisciplinary education perception scale and Readiness for interprofessional education scale. The results of need assessment will be summarized and a formal report will be prepared which will serve as a basis for planning and piloting IPE model in Orthodontics. Competency based IPE educational model will be designed by i) Identifying interprofessional competencies/learning outcomes in Orthodontics that may be achieved exclusively by interprofessional education. ii) Identifying assessment methods for the interprofessional competencies and aligning the curriculum with the interprofessional competencies. To evaluate the feasibility of competency based IPE educational model, it will be implemented in the form of a 2 day workshop entitled “Cleft Collaborative Care Best Practices Model (CCCBPM)”